2022
DOI: 10.3390/jcm11195660
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Poor Outcome in Sanders Type III and IV Calcaneal Fractures Treated with an Open Reduction and Internal Fixation with Plate: A Medium-Term Follow-Up

Abstract: Background: Consensus on the treatment for severely comminuted calcaneus fractures has yet to be found. This study aims to analyze the functional and radiological short- and medium-term outcomes of displaced calcaneus fractures of type III and IV treated with ORIF, and to identify, if present, the early predictors of unfavorable outcomes. Methods: Thirty-three calcaneal fractures were included, 23 type III and 10 type IV, according to Sanders classification. AOFAS scales for ankle and hindfoot and SF-12 were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The clinical outcome of our cohort was good (mean AOFAS score 80.8 ± 10.6). In line with the literature, the surgical treatment was effective and good to excellent outcome may be achieved, especially if compared with the nonoperative treatment [ 21 ] [ 22 ]. The mean AOFAS score was 84.4 ± 9.1 in the group A—patients with intact sustentacular fragment—and 74.3 ± 9.5 in the group B—patients with involved sustentacular fragment—with a significant difference between the two groups ( p < 0.001).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The clinical outcome of our cohort was good (mean AOFAS score 80.8 ± 10.6). In line with the literature, the surgical treatment was effective and good to excellent outcome may be achieved, especially if compared with the nonoperative treatment [ 21 ] [ 22 ]. The mean AOFAS score was 84.4 ± 9.1 in the group A—patients with intact sustentacular fragment—and 74.3 ± 9.5 in the group B—patients with involved sustentacular fragment—with a significant difference between the two groups ( p < 0.001).…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the relationship between the stability of the sustentacular fragment and the quality of reduction and fixation of fractures should be further investigated in the next future. The literature shows conflicting results both on outcomes of calcaneus fractures and the potential superiority of one treatment option over another or nonoperative treatment in complex calcaneal fractures such as Sanders type 3 and 4 fractures [ 22 ], without focusing on the involvement of the sustentaculum tali. Future researches will be necessary to investigate whether the involvement of the sustentaculum tali in the context of complex fractures may play a key role in driving treatment decisions toward either surgical or nonoperative strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, ORIF resulted in superior functional outcomes and greater patient satisfaction, with tolerable complication rates and no revision surgery required. Biz et al found that patients treated with open reduction and internal fixation techniques presented overall superior radiographic and functional outcomes compared with percutaneous approach [ 25 , 26 ]. Several minimally invasive techniques were developed for management of IACF; however, Ahmed Shams et al reported that treatment of displaced IACF with minimally invasive reduction and fixation using either cannulated screws or K-wires can achieve similar excellent functional and radiological outcomes, with high patient satisfaction, and additionally, K-wires has the advantage of reduced operative time [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcaneus fractures account for 1-4% of all fractures (60% of all tarsal fractures) [1], with 60-75% of them being displaced intra-articular calcaneal fractures (DIACFs) [2,3]. Nonsurgical treatment of patients with DIACFs frequently has poor functional outcomes due to secondary subtalar arthritis or malunion leading to variable periods of disability [4,5].…”
Section: Introductionmentioning
confidence: 99%